THE USE OF SONG LYRICS IN TEACHING LISTENING (A Case Study of Junior High School Grade 8 in Bandung) - Mellasari Hadian (Journal of English and Education, 2015)
This research entitled The Use of Song Lyrics in Teaching Listening (A Case Study of Junior High School Grade 8 in Bandung) was aimed at investigating the students’ response toward the use of song lyrics during the teaching of listening, and the challenges faced by the teacher and students in using song lyrics in listening class. This research employed qualitative method by involving a case study in one of junior high school in Bandung. The data were obtained through classroom observation and questionnaire. The data from classroom observation were obtained from video recording, student’s checklist and teacher’s field notes during the teaching program. The data analysis were presented in a form of descriptive explanation, and then the data collected from questionnaire were analyzed and summarized by using the frequency table, represented in graphs, then described the phenomenon found. The findings of this study showed the use of song lyrics as an effective technique for teaching listening. Significantly, it can be seen that the students enjoyed their listening activity. As a result, they responded positively and enthusiastically to the lesson, and engaged easily in the whole learning process.